Combined spine and pelvis injuries in children living in conditions of harmful impact of aluminium industry - M.B. Negreyeva; V.S. Kopylov; V.S. Ulyanov (Analiz Riska Zdorovʹû, 2016)
The orthopedic and x-ray studies of children of different ages with combined diseases of the spine and pelvis, living under constant effects of the harmful production factors induced by the aluminium production of Irkutsk region, have been conducted. The priority factor of exogenous risk to health is fluoride compounds. It has been established that in the structure of the combined pathology, the pelvis asymmetry ranks first, scoliosis ranks second, Legg – Calve – Perthes disease ranks third. According to the assessment of age structure of combined pathology we can conclude that at the equal manifestations of scoliosis, Spina bifida, retrospondylolisthesis, pelvis asymmetry, children of 11–15 y.o. more often have Legg – Calve – Perthes disease, children of 16–21 y.o. – coxarthrosis. We established statistically significant correlation between Legg – Calve – Perthes disease and age and sex of the children (Pearson's χ 2 at p < 0.01 makes 15.821 and 21.228 correspondingly). It’s important to mention that Legg – Calve – Perthes disease was registered in all examined boys and only in 35.5 % of girls. Correlation between this pathology and ecological factors was also statistically proved (χ 2 = 5.264, p < 0.05): within the radius of 5 km from the production facility the proportion of avascular necrosis was the highest (75 % cases). I and II degrees of manifestation of clinicoroentgenologic disorders of combined spine and pelvis pathology prevail. The relevance of further search for evidence of the relationship of chemical risk factors and the development of diseases of the musculoskeletal system was determined. Regular medical follow-up monitoring of children living in ecologically unfavorable territories in terms of early diagnosis of combined orthopedic pathology is recommended, including its premorbid period of development.